Характеристика функционального состояния гипофизарно-тиреоидной системы у больных хронической сердечной недостаточностью в зависимости от клинической эффективности санаторно-курортной реабилитации - Душкин, И.Ф. (Таврический медико-биологический вестник, 2013)
У хворих на хронічну серцеву недостатність, які перебувають на відновлювальному лікуванні в санаторії «Україна» (Гаспра, Крим), вивчено вміст гормонів гіпофізарно-тиреоїдної осі. Встановлено, що у хворих ХСН I ФК по NYHA відсутність клінічного поліпшення після відновного лікування в умовах спеціалізованих санаторіїв Південного берега Криму асоційована з вихідним (при вступі до санаторію) субклінічним «обривом» Т3-неогенеза – синдромом низького трийодтироніну. The hormonelevels of the pituitary-thyroid axis have beenstudiedin patients with chronic heart failureduringtheirrehabilitationatthesanatorium«Ukraine» (Gaspra,Crimea). It has been established that absence of clinical improvement in patients with NYHA FC I CHF post the rehabilitation treatment at the specialized pulmonary sanatoriums at the South Coast of the Crimea is associated with initial (on admission to the sanatorium) subclinical discontinuation of Т3-neogenesis – the low triiodothyronine syndrome.